2000
DOI: 10.1038/74255
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal adaptations to stress and impaired cardiovascular function in mice lacking corticotropin-releasing hormone receptor-2

Abstract: The actions of corticotropin-releasing hormone (Crh), a mediator of endocrine and behavioural responses to stress, and the related hormone urocortin (Ucn) are coordinated by two receptors, Crhr1 (encoded by Crhr) and Crhr2. These receptors may exhibit distinct functions due to unique tissue distribution and pharmacology. Crhr-null mice have defined central functions for Crhr1 in anxiety and neuroendocrine stress responses. Here we generate Crhr2-/- mice and show that Crhr2 supplies regulatory features to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
406
3
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(452 citation statements)
references
References 23 publications
32
406
3
11
Order By: Relevance
“…Ucn mRNA in the Edinger-Westphal (EW) nucleus is also increased in the CRFR2-mutant mice. The reported phenotype for these mice contains some discrepancies, because one group found a trend in anxiety levels in the mutant mice that did not reach significance (Coste et al, 2000), whereas another group only detected anxiety-like behavior in male but not female mutant mice (Kishimoto et al, 2000). Differences in breeding schemes and mouse strains have been proposed to explain the variation in results obtained for these mice.…”
Section: Abstract: Corticotropin-releasing Factor; Urocortin; Urocormentioning
confidence: 75%
See 1 more Smart Citation
“…Ucn mRNA in the Edinger-Westphal (EW) nucleus is also increased in the CRFR2-mutant mice. The reported phenotype for these mice contains some discrepancies, because one group found a trend in anxiety levels in the mutant mice that did not reach significance (Coste et al, 2000), whereas another group only detected anxiety-like behavior in male but not female mutant mice (Kishimoto et al, 2000). Differences in breeding schemes and mouse strains have been proposed to explain the variation in results obtained for these mice.…”
Section: Abstract: Corticotropin-releasing Factor; Urocortin; Urocormentioning
confidence: 75%
“…In direct opposition to the CRFR1-mutant mice, CRFR2-mutant mice display increased anxiety-like behavior and are hypersensitive to stress (Bale et al, 2000;Coste et al, 2000). These mice respond not only more rapidly to stress but also with greater amplitude, with mutant mouse corticosterone levels doubling control levels after 10 min of restraint (Bale et al, 2000).…”
Section: Abstract: Corticotropin-releasing Factor; Urocortin; Urocormentioning
confidence: 99%
“…In contrast, opiate-withdrawn CRF 2 receptordeficient mice display unaltered CRF 1 receptor-dependent neuroendocrine and behavioral responses (Ingallinesi et al, 2012;Papaleo et al, 2008), suggesting that resilience to the stress-induced reemergence of motivational alterations is specifically because of the lack of functional CRF 2 receptors. The CRF 2 receptor has been largely implicated in the stress response (Bale et al, 2000;Coste et al, 2000;Kishimoto et al, 2000). However, herein drug-naive mice of either genotype do not differ following exposure to the FWS or the EPS.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…For example, it was demonstrated that CRF transgenic mouse lines overexpressing CRF exhibited a behavioral state resembling that produced by anxiety in the elevated plus-maze and the light/dark tests [82]. Moreover, three recent studies reported that male, but not female, CRF 2 receptor-deficient mice exhibit enhanced anxious behavior in several tests of anxiety, including the elevated plus-maze, the light/dark and the open-field tests [3,22,48]. Finally, CRF-binding protein-deficient mice were shown to exhibit a significant increase in a fear-related behavior in the elevated plus-maze, open-field and defensive withdrawal tests [46,71].…”
Section: Mouse Models Of 'Pathological' or 'Trait' Anxietymentioning
confidence: 99%